2012
DOI: 10.1016/j.eswa.2011.10.014
|View full text |Cite
|
Sign up to set email alerts
|

Consistency maintenance for evolving feature models

Abstract: a b s t r a c tSoftware product line (SPL) techniques handle the construction of customized systems. One of the most common representations of the decisions a customer can make in SPLs is feature models (FMs). An FM represents the relationships among common and variable features in an SPL. Features are a representation of the characteristics in a system that are relevant to customers.FMs are subject to change since the set of features and their relationships can change along an SPL lifecycle. Due to this evolu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 30 publications
(81 reference statements)
0
32
0
Order By: Relevance
“…Then, one will have to adapt the feature model comparison process to support that new classification. Previous work on feature models showed that their maintenance can be complex and error prone [5,15]. With an approach such as FMDiff, it would be possible to extract new information about the evolution of the features using already existing artefacts, at the cost of adapting our tool.…”
Section: Threats To Validitymentioning
confidence: 99%
See 1 more Smart Citation
“…Then, one will have to adapt the feature model comparison process to support that new classification. Previous work on feature models showed that their maintenance can be complex and error prone [5,15]. With an approach such as FMDiff, it would be possible to extract new information about the evolution of the features using already existing artefacts, at the cost of adapting our tool.…”
Section: Threats To Validitymentioning
confidence: 99%
“…Feature model evolution has been extensively studied in the past [15,26,41,44]. These studies provide insights on which operations may occur on features, detailed examples of transformations occurring on large scale product linesindustrial and open source, and the evolution of feature model structural metrics (number of leaves, nodes, constraints).…”
Section: Introductionmentioning
confidence: 99%
“…While the evolution of Boolean fms as been widely studied in the literature [12,1,16,14,10,28,19,26,18,17], little is known about cardinality-based fm evolution. For instance, cloud environments evolve over time, e.g., when a new service support is available or the provided amount of resources has been extended.…”
Section: Motivating Examplementioning
confidence: 99%
“…Several approaches address fm analysis [2], e.g., to detect inconsistencies that can arise during specification and evolution of fms. Other work discusses edits (changes) on fms during evolution, e.g., with respect to the resulting set of products [28], the mappings to solution space [26] or fm consistency [10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation